Knowledge conceptualization and software agent based approach for OWL modelling issues - Zhao, Shuxin; Wongthongtham, Pornpit; Chang, Elizabeth; Dillon, Tharam S. (Springer, 2008)
In this paper, we address the issues and solutions of using OWL to model the knowledge captured in relational databases. Some types of knowledge in databases cannot be modeled directly using OWL constructs. Two alternative approaches are proposed with examples of two types of knowledge. Firstly the data value range constraint and secondly the calculation knowledge representation. The first approach to the problem is to conceptualize the data range as a new class and the second solution to the problem is proposed, based on utilizing software agent technology. Examples with OWL code and implementation code are given to demonstrate the problems and solutions.